Effects of aging and involuntary capture of attention on event-related potentials associated with the processing of and the response to a target stimulus - Cid-Fernández, Susana; Lindín, Mónica; Díaz, Fernando (Frontiers in Human Neuroscience, 2014)
The main aim of the present study was to assess whether aging modulates the effects of involuntary capture of attention by novel stimuli on performance, and on event-related potentials (ERPs) associated with target processing (N2b and P3b) and subsequent response processes (stimulus-locked Lateralized Readiness Potential -sLRP- and response-locked Lateralized Readiness Potential -rLRP-). An auditory-visual distraction-attention task was performed by 77 healthy participants, divided in three age groups (Young: 21-29, Middle-aged: 51-64, Old: 65-84 y. o.). Participants were asked to attend to visual stimuli and to ignore auditory stimuli. Aging was associated with slowed reaction times, target stimulus processing in working memory (WM, longer N2b and P3b latencies) and selection and preparation of the motor response (longer sLRP and earlier rLRP onset latencies). In the novel respect to the standard condition we observed, in the three age groups: (1) a distraction effect, reflected in a slowing of reaction times, of stimuli categorization in WM (longer P3b latency), and of motor response selection (longer sLRP onset latency); (2) a facilitation effect on response preparation (later rLRP onset latency), and (3) an increase in arousal (larger amplitudes of all ERPs evaluated, except for N2b amplitude in the Old group). A distraction effect on the stimulus evaluation processes (longer N2b component) were also observed, but only in middle-aged and old participants, indicating that the attentional capture slows the stimulus evaluation in WM from early ages (from 50 years onwards, without differences between middle-age and older adults), but not in young adults.